Upaya Peningkatan Pengatahuan dan Pemahaman Gigi Tiruan bagi Lansia dan Kader Posyandu Lansia Kemuning 1 Kelurahan Menteng Atas Jakarta Selatan - Mujiwati, Mujiwati; Wiyanti, Sri Wiwik; Fitriyanti, Fitriyanti (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The elderly is the final stage in life, which is characterized by many changes, and one of them is tooth loss, which causes disruption to masticatory function, temporomandibular joint (TM) function, and psychological, namely aesthetics and speech function. Aim this community service is increase knowledge of elderly and cadres about maintaining dental health and role of dentures. Implementation method with pre-post tests, lectures and delivery of educational videos about maintaining dental health and the role of dentures for dental and oral health at Posyandu Lansia Kemuning 1, Menteng Atas Village, South Jakarta. Participants in this activity consisted of 35 elderly people, 5 cadres and involved 2 students involving the RT and RW head partners. That was an increase in knowledge from the good category of 5.7% to 82.9%, previous sufficient knowledge from 14.3% to 17.1% and 80% of people with less knowledge to no knowledge. The conclusion is a significant increase in knowledge of cadres and public about role of dentures and oral health and interest of elderly in making dentures as tooth replacements. It is hoped that this program can continue through cadres who have been provided with education through leaflets and videos that have been given to elderly and pre-elderly.